MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN ATEMATIKA MELALUI MEDIA DADU BAGI ANAK TUNARUNGU DI KELAS D II B SLB SYEKH MUHAMMAD SA’AD MUNGKA - Indrawati - - (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the problems of children with hearing impairments D class II B in SLB Shaykh Muhammad Sa'at Mungka dalammelakukan where the child had difficulty summing up to 20 numbers, so far the work done in membelajarkan child's teacher using the media sticks, stones and the abacus, but the effort was a teacher not bring the expected results. The purpose of this study is to improve the ability of the sum of numbers to 20 through the medium of the dice in class D II B SLB Syekh Muhammad Sa'ad Mungka. Learning ability of the sum of numbers in mathematics through the media is done by matching dice dice with dots correspond to numbers in addition problems and do the sums by calculating the point of the combined dice and write the sum of numbers, it is intended that the child can do the summation of numbers to 20. This study aimed to: 1) describe the use of media in raising the sum of the dice numbers of children with hearing impairment, and 2) know the achievements of children with hearing impairments D II B in SLB syekh Muhammad Sa'ad Mungka in increasing numbers the sum of the results to 20 through the medium of the dice. This research methodology was action research class (classroom action research) is done in the form of collaboration. These actions are taken to two deaf children who become research subjects.